MICROSATELLITE EXPANSION – MOLECULAR-BIOLOGICAL PHENOMEN OF DIAGNOSIS PRECANCEROUS AND CANCEROUS PROCESSES - Харченко, О.В. (World of Medicine and Biology, 2015)
Relative saturation of genomes with any microsatellite sequences is the result of influence of many factors, which all in all determine composite, structural and thermodynamic features of genomic microsatellite sequences. Polymorphism of microsatellites can be identified by their morphological characteristics. The difference in the degree of polymorphism between various microsatellites may depend first on the length of microsatellite sequence it self. Intensive extension of microsatellite sequences due to replication errors is called microsatellite expansion. The ability of repeats to expansion depends on the length of microsatellite sequence. The relations between mutative events, leading to expansion of microsatellite sequences due to addition of a repeat, correlates with number of mutations, which lead to reduction of repeats in human microsatellites as 10:4. Polymorphism of microsatellites can be identified by their localization and orientation in genome. The secondary structure of DNA is currently viewed as the cause of expansion of microsatellite sequences. The secondary structure of DNA itself is the derivative of thermodynamic characteristics of its sequence. The secondary bulge-type structures in microsatellite sequences, identified by their thermodynamic characteristics, can initiate the phenomenon of expansion of microsatellite repeats. The more stable these bulges, the lower is the risk of formation of new microsatellite repeats. Calculations of thermodynamic characteristics of replicable sequences allow developing number of model systems, evaluating the ability of microsatellite sequences to influence the DNA modifications, forming various secondary structures, related to phenomenon of expansion of microsatellite repeats. Types of markers, obtained as a result of PCR, are divided into two groups on the basis of primers’ design: the first group is known as STSs (sequence-tagged sites) with primers, constructed from known sequences, and the second one is based on the random primers. The most informative or polymorphic STS-marker emerges during amplification of DNA-area, containing sequences of microsatellite repeats. This marker is based on STS, and is marked as simple-sequence length polymorphism (SSLP) or sequence-tagged microsatellite site (STMS). Each STMS-marker detects inherited codominant alleles in single locus in genome.